Beachwear adaptável: um estudo para diferentes tipos de corpos femininos - Martins, Estela Munhoz (2016)
This project aims to adapt parts of different biotypes beachwear segment to existing female. From experimental studies the project seeks to develop parts who bring innovation in modeling through application and ergonomic design innovation. For both, will be carried out a study of the various types of the female body and how they behave with existing parts on the market. As main result is expected to develop a product that has a functional and aesthetic quality.